Impact of Prolonged Frozen Storage on ‘Mejhoul’ Date Palm Cultivar Based on Selected Qualitative Characteristics - Younes Noutfia; Ewa Ropelewska; Justyna Szwejda-Grzybowska; Zbigniew Jóźwiak; Monika Mieszczakowska-Frąc; Krzysztof P. Rutkowski (Horticulturae)
In contrast to previous studies investigating the effect of freezing at low temperatures, this work aimed to evaluate the quality of ‘Mejhoul’ during the long-term storage of 8 months under freezing at −10 °C and −18 °C. Based on numerous physicochemical attributes and image features, the behavior of ‘Mejhoul’ was assessed at 0, 2, 4, 6, and 8 months of frozen storage. The quality characteristics examined included polyphenols, sugars, color parameters, hardness, water loss, defects, and image features. The results exhibited a significant increase in water activity after eight months of frozen storage. pH increased in a similar way for both storage conditions, while titratable acidity decreased significantly. All color attributes (L*, a*, and b*) were not influenced by frozen storage, while hardness decreased significantly after eight months. Phenolic acids decreased significantly at the end of frozen storage for both freezing temperatures. However, total polyphenols, flavonoids, total sugars, glucose, and fructose were not affected by the prolonged frozen storage. Furthermore, this investigation showed a slight water gain at both storage temperatures, with a pronounced occurrence rate of skin separation for ‘Mejhoul’ stored at −18 °C. Finally, the clustering analysis exhibited a high linkage distance between the examined groups at frozen storage at −10 °C compared to −18 °C.